Phytochemical Screening and Antioxidant Capacity of Some Selected Medicinal Plants of Bangladesh - Karim, Md Masudul; Fakir, Md Faruk; Sagar, Ashaduzzaman; Murshed, H M Munjur; Ashrafuzzaman, M (Bangladesh Journal of Botany, 2024)
Medicinal plants are very much known for the presence of high amounts of different phytochemicals. Leaves of twelve medicinal plants, Andrographis paniculata, Blumea lacera, Caesalpinia bonduc, Codariocalyx motorius, Hyptis suaveolens, Vitex trifolia, Centella asiatica, Cynodon dactylon, Portulaca oleracea, Hyptis capitata, Acmella paniculata and Lippia alba grown in the Bangladesh Agricultural University Botanical Garden, had been selected to investigate the presence and status of different phytochemicals along with the antioxidant activity. This article revealed that all of these medicinal plants contained high amounts of different phytochemicals. The phenolics contents ranged from 118.98– 288.62 mg GAE/ 100 g FW, flavonoids (95.19– 198.51 mg QE/ 100 g FW), FRAP values (0.4523– 3.4390 µmol Fe2+/ g FW), IC50 values– amounts required to scavenge DPPH radicals (3.376– 38.56 mg/ mL), vitamin- C (10.418– 41.763 mg/ 100 g FW), total chlorophyll (0.7818– 4.2185 mg/ 100 g FW), carotenoids (0.4614– 1.8557 µg/ g FW), and among which, H. suaveolens and H. capitata from the Lamiaceae family showed the best performances regarding the most of the parameters. Based on the results of the present investigation, it may be concluded that these medicinal plants possess excellent amounts of different phytochemicals and are a good source of antioxidants, which indicates their potential in various ethnomedicinal studies and therapeutic uses. Bangladesh J. Bot. 53(2): 373-380, 2024 (June)